Comparing different dimensions of clinical perfectionism in medical and non-medical students of Shahid Beheshti University of Tehran in 2019 - Yaseri, Aram; Kianimoghadam, Amir Sam Kianimoghadam; Bakhtiari, Maryam (Researcher Bulletin of Medical Sciences, 2024)
Abstract Perfectionism is a set of very high standards of performance that is accompanied by self-assessments of negativity, criticism, and blame. According to some classifications, perfectionism is based on three dimensions of self-oriented perfectionism (the tendency to set strict and unrealistic criteria for itself and focus on defects and failures in performance along with precise self-monitoring), other-oriented (the tendency high standards for others, and high and irrational expectations from them) and socially prescribed perfectionism (the perceived need for perceptions to meet the expectations and standards prescribed by the society and others) are categorized and evaluated. Students in a community, like other classes in a community, will have such high expectations of themselves, others, and the society as a whole, but what matters is how much perfectionism can affect the field of study and, in particular, the work and social aspects of the individual. What we did in this cross-sectional study was using the Tehran multidimensional perfectionism questionnaire to evaluate and compare the three dimensions of perfectionism in a specified number of medical and non-medical students of Shahid Beheshti University of Medical Science in 2019. As a conclusion, among the three dimensions of perfectionism, the dimension of self-oriented perfectionism was more bolded among medical students and other-oriented perfectionism is more evident among non-medical students. Socially prescribed perfectionism seems to be similar in both groups.